CHANGES IN THE PROPERTIES OF ELASTICITY IN THE TECHNOLOGICAL PROCESSES OF SPINNING YARN FROM COTTON FIBER AND WEAVING FABRIC (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
This study examines the changes in the elasticity properties of cotton fibers during the technological processes of spinning yarn and weaving fabric. It analyzes how mechanical stresses, such as drafting, twisting, tension, and friction, alter fiber elasticity and affect the quality of the final textile product. Spinning processes lead to reductions in fiber elasticity due to molecular realignment and compression forces, while weaving introduces additional deformation through tension and friction. The cumulative effects result in up to a 30% reduction in fiber elasticity. Strategies for optimizing process parameters, such as controlling twist levels, drafting ratios, and weaving tensions, are explored to preserve fiber elasticity. This research emphasizes the importance of process optimization in enhancing fabric performance and ensuring the sustainability of cotton textiles.